NMR of Biomolecules. - Bertini, Ivano (John Wiley & Sons, 2012)
NMR is one of the most powerful methods for imaging of biomolecules. This book is the ultimate NMR guide for researchers in the biomedical community and gives not only background and practical tips but also a forward looking view on the future of NMR in systems biology.